2015
DOI: 10.1128/jvi.03264-14
|View full text |Cite
|
Sign up to set email alerts
|

ORF57 Overcomes the Detrimental Sequence Bias of Kaposi's Sarcoma-Associated Herpesvirus Lytic Genes

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) encodes ORF57, which enhances the expression of intronless KSHV genes on multiple posttranscriptional levels. However, it remains elusive how ORF57 recognizes viral RNAs. Here, we demonstrate that ORF57 also increases the expression of the multiple intron-containing K15 gene. The nucleotide bias of the K15 cDNA revealed an unusual high AT content. Thus, we optimized the K15 cDNA by raising the frequency of GC nucleotides, yielding an ORF57-independent version. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 68 publications
3
26
0
Order By: Relevance
“…Screening the target RNAs for the previously identified ORE was not successful . This is consistent with a similar bioinformatic analysis performed by our group which also failed to identify putative OREs in other ORF57 dependent genes . In sum, both studies extend the list of viral and cellular ORF57 targets, but the exact mode of recruitment still remains unclear.…”
Section: Rna Recognition By Orf57supporting
confidence: 84%
See 1 more Smart Citation
“…Screening the target RNAs for the previously identified ORE was not successful . This is consistent with a similar bioinformatic analysis performed by our group which also failed to identify putative OREs in other ORF57 dependent genes . In sum, both studies extend the list of viral and cellular ORF57 targets, but the exact mode of recruitment still remains unclear.…”
Section: Rna Recognition By Orf57supporting
confidence: 84%
“…In our experimental system we used K15 and ORF47 as reporters for ORF57 activity and observed an up to 30 fold increase in nuclear RNA levels. Export was detectable but only to a minor degree . The situation may be similar to most transient transfection experiments where also intron‐less cDNAs are expressed in the absence of splicing.…”
Section: Rna Recognition By Orf57supporting
confidence: 60%
“…Differential GC content, the presence of specific RNA motifs in responsive transcripts, atypical codon usage, and differential transcriptional activation have all been proposed to explain specificity of action of SM homologs (33,36,46,(51)(52)(53). Our data demonstrate that while the basis for SM responsiveness does appear to reside in the coding sequences of the relevant genes, there is no clear relationship of the SM effect to any of the above characteristics in the SM-dependent gene set.…”
Section: Discussionmentioning
confidence: 42%
“…8A). It has been suggested that one basis for the gene specificity of the KSHV SM homolog ORF57 is the GC content of its target genes (33). While the SM-dependent gene set had a slightly lower GC content than the comparator sets of SMindependent genes, all other lytic genes, or latent genes, the average values were not overtly different (Fig.…”
Section: Identification Of Ebv Sm-dependent Rna Expression During Ebvmentioning
confidence: 83%
“…The mechanism by which ORF57 selectively increases their expression remains unclear, as it depends on the sequence of the coding region rather than promoter sequences or polyadenylation signals [85]. Interestingly, Vogt et al found a similar effect, reporting that ORF57 is required to sustain the levels of some viral mRNAs containing higher AT nucleotide content, which they propose is suboptimal compared to cellular nucleotide content [86]. In a separate study vFLIP was demonstrated to have suboptimal codon usage, which impaired vFLIP RNA accumulation [87].…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%